URGENCY CRITICAL LEGAL STUDIES PARADIGM FOR THE PROTECTION OF WOMEN VICTIMS OF DOMESTIC VIOLENCE IN THE DIVORCE CASE - Triana, Nita (Syariah: Jurnal Hukum dan Pemikiran, 2018)
This research describes the protection of women victims of domestic violence in divorce cases. Domestic violence victims are hidden in divorce cases in the Religious Courts. The positivistic paradigm adopted by the Judges gives less protection to victims of domestic violence. The method used in this study is a qualitative method, a type of doctrinal legal research with a socio-legal  approach. Domestic violence victims in the Religious Courts need a new paradigm to provide protection for victims of domestic violence. Religious Court Judges who have a positivistic paradigm see the law as a book (act). The judge in examining the domestic violence in divorce only adheres to the law relating to marriage, namely Law No. 1 of 1974 and Compilation of Islamic Law. Paradigm of Critical Legal Studies. build critical awareness in law enforcement by improving the legal system and carrying out a reformation in the institutions responsible for the protection of victims of domestic violence, one of which is the Religious Courts. Also consider the PKDRT Law No. 23 of 2004 concerning the elimination of domestic violence even covering legal culture of family, community, health and psychological.